(untitled) (Journal of Universal Science Research, 2024)
The study of fluid flows in channels is of paramount importance in various engineering and environmental applications. To address the complex nature of these flows, numerical methods have become an invaluable tool for understanding and analyzing flow behavior. The Finite Element Method (FEM) is one such numerical technique that has gained widespread acceptance due to its versatility and robustness in handling diverse fluid flow problems. In this article, we present the development of a novel numerical algorithm based on the Finite Element Method tailored for the study of flows in channels. We discuss the underlying principles, implementation, and applications of this algorithm, showcasing its capabilities in simulating and analyzing channel flows with high accuracy.